CYBERSECURITY AND INTERNET OF THINGS - Čapek, Jan (Trauner Verlag, 2018)
Introduction of computers in all spheres of life substantially changed the ways of how people communicate and exchange information. It is creating a virtually paperless work environment. The Internet of Things (IoT) makes the connection between the real world and the virtual world stronger than ever before. The objective of computer security and or IoT includes protection of information and property from theft, corruption, or natural disaster, while allowing the information and property to remain accessible and productive to its intended users. IoT has become a ubiquitous term to describe the tens of billions of devices that have sensing or actuation capabilities, and are connected to each other via the Internet. Security has not been a high priority for these devices until now.
Kybernetická bezpečnost a Internet věcí
Keywords: Cybersecurity; Internet of Things; Geoencrypting; Encrypting and decrypting methods; Kybernetická bezpečnost; Internet věcí; Geošifrování; Šifrování a dešifrování